2014
DOI: 10.1209/0295-5075/105/31002
|View full text |Cite
|
Sign up to set email alerts
|

Topologically stable gapped state in a layered superconductor

Abstract: We show that a layered superconductor, described by a two-component order parameter, has a gapped state above the ground state, topologically protected from decay, containing flow and counter flow in the absence of an applied magnetic field. This state is made of skyrmions, breaks time reversal symmetry and produces a weak local magnetic field below the present threshold of detection by µSR and NMR/NQR. We estimate the density of carriers that condense into the pseudogap.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Thus the state has a lower symmetry than the theory itself, a situation commonly seen in physics in the context of the Goldstone theorem 52 . The three term decomposition of the kinetic energy is general and can be applied in other situations such as in the Ginzburg-Landau approach to layered superconductors [53][54][55][56][57] where the pseudogap can be interpreted as a topological state 58 .…”
Section: The Weyl State and The Breaking Of The Space-time Symmetriesmentioning
confidence: 99%
“…Thus the state has a lower symmetry than the theory itself, a situation commonly seen in physics in the context of the Goldstone theorem 52 . The three term decomposition of the kinetic energy is general and can be applied in other situations such as in the Ginzburg-Landau approach to layered superconductors [53][54][55][56][57] where the pseudogap can be interpreted as a topological state 58 .…”
Section: The Weyl State and The Breaking Of The Space-time Symmetriesmentioning
confidence: 99%
“…Although the above scheme contains the basic sought ideas, it does not unfold the topological stable solutions that exist in the layered system. To unveil them a dual view of the kinetic energy [21] must be obtained, as shown in the next section.…”
Section: The Theorymentioning
confidence: 99%
“…Recently we have shown that an above the homogeneous (normal) state gap and the broken symmetries can be understood in the context of an order parameter description, and for this reason, suggested this interpretation for the pseudogap [21]. Thus the pseudogap is a gapped topological state made of skyrmions, whose microscopic nature is still controversial.…”
Section: Introductionmentioning
confidence: 98%
“…The carriers have spin, charge, and an effective p-1 arXiv:1708.05491v1 [cond-mat.supr-con] 18 Aug 2017 mass in the kinetic energy described by the non-relativistic gauge invariant Schroedinger equation. We show that these electronic states can display a Dirac linear spectrum by becoming Weyl states [24], which are two-dimensionally confined in momentum but not in position space. The Weyl equation is reinterpreted here according to its space and time symmetries and shown to have a cutoff in momentum space, such that a linear dispersion spectrum exists much above it.…”
mentioning
confidence: 93%